ANALYSIS OF DIFFERENT PATTERNS OF DIURNAL WIND SPEED DURING WET AND DRY SEASONS (CASE STUDY: HAMBA PRAING, SUMBA ISLAND) - Ichsana, Dwikita
Based on the preliminary analysis on wind speed data obtained from the meteorological tower installed in Hamba Praing, Sumba Island, there are differences in variations in diurnal wind speed patterns between the wet and dry seasons. In the wet season, the diurnal wind speed pattern is maximum during the day or can be called a diurnal pattern. Meanwhile, in the dry season, the diurnal wind speed pattern is maximum in the morning and evening or can be called a semidiurnal pattern. However, the cause of the difference in the diurnal wind speed pattern is still unknown. In this study, the observation wind speed data obtained from the meteorological tower from October 2012 – December 2015, and Final Analysis (FNL) data were used as input to the WRF model simulation. In the observation wind speed data, a quality control process is carried out to eliminate the tower shading effect. Then, the study time was chosen to be simulated by performing diurnal harmonic analysis to see the frequency amplitude of the occurrence of diurnal and semidiurnal patterns. After that, a simulation is carried out using the WRF model and verification of the WRF output to see the suitability of the WRF output diurnal wind speed pattern with the climatological diurnal wind speed pattern. Because the study location is in a coastal area, then the identification of the influence of the land-sea breeze is carried out by decomposing the horizontal wind speed, calculating the land-sea temperature gradients, and analyzing net surface energy to explain the time/phase of the temperatur difference that occurs. The results of this study indicate that when the diurnal wind speed is maximum, sea breezes occur. In the wet season, when the wind speed reach maximum is followed by the maximum land-ocean temperature difference. Meanwhile, in the dry season, when the wind speed reach maximum is not followed by a maximum temperature difference, but the time/phase shifts. This temperature difference occurs because there is a difference in the net surface energy which is heavily influenced by the net surface radiation factor, with the largest contribution being from downward shortwave radiation.